Solar-Fuel-Cell Hybrid System Control Strategy Oriented for Off-Grid Systems - Ajweh, Shadi; Ajarmeh, Mohammad (جامعة بوليتكنك فلسطين - كلية الهندسة - ميكانيك, 2013)
Socio-economic development requires delivering electrical energy efficiently either form traditional or renewable sources. The final cost of delivering this energy depends on the many factors, which include economic and environment impacts. This has led to attract more attention to renewable energy sources and to develop its applications. However, each source is efficient only for specific situations and applications. Thus, integrating different renewable sources could provide more effective solutions. This trend requires the development of energy management and control strategies, especially when off-grid applications are the target. The geographical location of Palestine lies within a considerably high solar belt, which is up to 5-6 kWh solar energy falling per square meter per day, and sunshine is about 3000 hour per year. Fuel-cell and hydrogen fuel technologies have attracted special attention due to their potential for replacing traditional internal combustion engines that runs on fossil fuels. Fortunately, hydrogen could be generated from bio-waste material available locally using economic technologies. This contribution will introduce a control strategy for effective integration of fuel-cell and solar energy oriented for off-grid systems. The effectiveness of the proposed strategy will be proved using MatLab/Simulink software for applying solar-fuel-cell hybrid system on a study case. A typical energy consumption pattern for a Palestinian home will be used. In addition, the project will provide a sizing and optimization of system using PSO algorithm, also a modeling of the proposed system. Experimental results obtained for a reduced scale model parts built in the lab to give insight into the system technical details. فكرة المشروع تقوم على تطوٌر استراتٌجٌة تحكم فً طاقة النظام الهجٌن الذي ٌستخدم كال من الخالٌا الشمسٌة وخالٌا الهٌدروجٌن باالضافة الى البطارٌات النتاج الطاقة، سٌتم اثبات فعالٌة هذه االستراتٌجٌة باستخدام برناج الماتالب لتطبٌقها على حالة حقٌقة لبٌت فً جنوب فلسطٌن ودراسة نتائجها. اٌضا فً هذا المشروع تم استخدام نظرٌة سرب الطٌور لتحدٌد الحجم األمثل لكل جزء فً النظام بهدف تقلٌل التكلفة وزٌادة االعتمادٌة على النظام، باالضافة الى عمل models باستخدام الماتالب لكل جزء فً النظام. بعد ذلك تم عمل نموذج فً المختبر بهدف محاكاة النظام الحقٌقً وتم فٌه تثبٌت الجهد ب 1.2 فولت لٌحاكً الجهد فً المنزل 220 فولت.
CD , no of pages 111 , 26832, ميكانيك 7/2013 , in the store
Keywords: Solar-Fuel-Cell Hybrid System Control